Potentially peat‐forming biomass of fen sedges increases with increasing nutrient levels. (11th May 2021) - Hinzke, Tjorven; Li, Guixiang; Tanneberger, Franziska; Seeber, Elke; Aggenbach, Camiel; Lange, Jelena; Kozub, Łukasz; Knorr, Klaus‐Holger; Kreyling, Juergen; Kotowski, Wiktor
Abstract: Peat formation is a key carbon sequestration process in the terrestrial biosphere. In temperate fens, peat is mainly formed by below‐ground biomass of vascular plants. Nutrient availability in temperate fens is naturally variable, and nowadays increasing due to atmospheric deposition, runoff from agriculture and mineralization of peat caused by drainage. To maintain or restore peat formation, it is important to understand how increased nutrient availability influences the main controls of peat formation, that is, below‐ground biomass production and decomposition. We investigated above‐ and below‐ground biomass production and decomposition of five fen sedges ( Carex spp.) grown under 12 different nutrient levels (realized with nitrogen amounts increasing exponentially across levels, with addition of phosphorous and potassium to ensure nitrogen limitation in each nutrient level) in a mesocosm experiment, designed to resemble a gradient of very low to very high nutrient availabilities in temperate fens. In addition, we measured nutrient stoichiometry in the biomass and related this to possible growth limitations and to root decomposition. Our results indicate that higher biomass production at higher nutrient levels was not offset by an increase in decomposition. Increase of above‐ and below‐ground biomass with higher nutrient levels was species‐specific. Decomposition of standardized plant material in mesocosms was not dependent on the species growing in the mesocosms and showed only slight, if any, variation with differing nutrient levels. Decomposition of roots grown under different nutrient levels was mainly correlated with species identity and root lignin:cellulose ratio. Our study suggests that the Carex spp. potentially peat‐forming root biomass, here defined as the root biomass which is not decomposed during one growing season, increases with increasing nutrient levels: higher root biomass production is not counteracted by increasing decomposition during the growing season. Based on this pattern of positive mass balance in five common sedge species with differing growth characteristics, we propose that sedge communities establishing after rewetting have the potential for renewed peat formation regardless of the prevailing trophic level. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.